Case report: Cervical arterial dissections in the setting of recent COVID-19 infection - Lim, Sanghee; Rode, Matthew M.; Keser, Zafer; Flemming, Kelly D. (Frontiers in Stroke, 2024)
Background: COVID-19 infections have been implicated in cerebral ischemia, but their relationship to cervical arterial dissections remains poorly characterized. Descriptions of cervical arterial dissections in patients with COVID-19 infections with details regarding their presenting symptomatology, imaging findings, and responses to treatment with antithrombotic therapy may be helpful to clinicians.Methods and Observations: We present six adult cases of cervical arterial dissections in the setting of recent COVID-19 infections from 2021-2022 at our institution. Four cases presented with dissections involving the internal carotid artery, while two cases had dissections of bilateral vertebral arteries. In one patient, we found imaging evidence for a possible inflammatory process. All patients were treated with either antiplatelet agents or direct oral anticoagulants.Conclusions and Relevance: COVID-19 infections may predispose patients to spontaneous cervical arterial dissections. Such patients can have variable neurologic presentations, though headaches and neck pain were common complaints. Most patients responded well to antithrombotic therapy, with improvement in symptoms and radiologic findings at follow-up. Clinicians should maintain a high degree of suspicion for cervical arterial dissections in patients who present acutely with severe headache/neck pain and/or new neurologic deficits in the setting of COVID-19 infections.